"Water running in my chest": Delayed spontaneous rupture of an aortocoronary saphenous vein graft aneurysm. Issue 4 (4th March 2021) - Gnall, Eric; Jayanna, Manju Bengaluru; Shapiro, Timothy; Abdulbasit, Muhammad; Drosou, Maria Elena; Ahmad, Tariq
Abstract: Saphenous vein graft aneurysm is an uncommon condition and knowledge about its natural history, and a multi‐specialty heart team approach is of utmost importance for better clinical outcomes. This case highlights importance of percutaneous intervention as a viable therapeutic option in the case of saphenous vein graft aneurysms. Abstract : Saphenous vein graft aneurysm is an uncommon condition and knowledge about its natural history, and a multi‐specialty heart team approach is of utmost importance for better clinical outcomes. This case highlights importance of percutaneous intervention as a viable therapeutic option in the case of saphenous vein graft aneurysms.